Observing high quality children's residential care : reflecting on an implementation approach - Mihaela Manole; Laura Quinn; Gemma Watson (Scottish Journal of Residential Child Care)
Delivering high-quality residential care to children requires skilled, knowledgeable, and reflective practitioners who are supported to continuously learn and develop. In collaboration with Aberlour Sycamore Children’s Houses, we explored how a practice profile of learnable, teachable, doable, and assessable residential child care practice could be used to support practice across two of the houses. We explored how a structured approach to observation and feedback could help to grow and develop residential childcare practice. In order to assess the impact of this work across house staff teams, senior managers and project team members, we undertook a series of ‘sailboat retrospective’ sessions. This highlighted how a whole system approach, leadership support, and a sense of shared ownership helped to cement this work, improving practice for young people and professional development for staff.